MINISTRY OF FINANCE OFFICE COMPLEX IN KIPP-IKN WITH A BIOMIMETIC APPROACH BASED ON TRANSIT-ORIENTED DEVELOPMENT - Muhammad Maskur; Respati Wikantiyoso; Nurhamdoko Bonifacius (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
The Indonesian government is taking significant steps in developing the Nusantara Indonesian Capital (IKN) in Kalimantan, focusing on economic equality and sustainable development. Development of the core government center (KIPP) is a priority, with infrastructure development focused on Phase 1A (2024) and Phase 1 (2025-2029). The Ministry of Finance plays an essential role in this area, with plans to build the Ministry of Finance Office Complex (KPKK) regulated in Presidential Regulation Number 63 of 2022. However, until now, the government has not issued a basic engineering design. Opportunity to propose a Ministry of Finance Office Complex design that supports IKN's vision and mission. The TOD-based Bio-mimetic KPKK design is expected to fulfill the principles of KIPP development. Bio-mimetic, with inspiration from nature and TOD that integrates various modes of transportation and accessibility, provides an innovative approach to design. Implementing these concepts can support IKN as a creative, modern, and sustainable city while ensuring effective regional connectivity.